Benchmarking in logistic centres' environment - Kampf, Rudolf; Roudná, Jana (Univerzita Pardubice, 2008)
This paper deals with topic the benchmarking in logistic centres' environment The benchmarkingtest should help to logistic centres with gaining objective data, which are necessary formaking strategie decisions.General strategy of the company intluences singnificantly choice of key indicators of the performance, which we want to measure.Setting the right indicators is not easy, because the unsuitable choice can cause that gained frame of the company (Iogistic centre) is not right. In the paper there are used fractiles for setting the company's position, in the concrete the median, which is basic type of the fractiles.
Benchmarking v prostředí logistických center
Benchmarking in der Umwelt der logistischen Zentren